An Informal Affiliation Model: Socio-Educational Practices of the Students of the Interuniversity Headquarters of Alajuela - Cavallini Solano, Hennia María (2018)
This article is the output generated/produced of one of the research’s dimensions of analysis called ‘’The individuals’ capabilities in/from the community that guide the curriculum’s formulation of the Mechanical Engineering’s Career with the emphasis on fire protection at the Alajuela’s inter- university center.’’ In this article is sought to unveil the affiliate university model adopted or taken by the student population, tool that will serve as a base for the Mechanical Engineering’s curriculum reformulation with emphasis on fire protection. This model of affiliation is associated with the capacity of affiliation and is unveiled as a socio-educational practice. The methodological approach of this work is of a mixed type, in which were used different observation strategies and interviews. They allowed tackling by means of a voting system and the Net Draw programme the graphical construction of maps of affiliation. The main/key findings involve or are related to an informal model’s characterization of a short-term horizontal chaining, dependent on the spacing area.